Ergonomic Design Strategy for Crutches of a Lower-limb Exoskeleton for Paraplegic Individuals: An Experimental Study. (September 2018) - Han, Jimin; Jin Hyun, Dong; Jung, Kyungmo; Yoon Kim, Kye; Youn, Seokyoung
This paper presents a design strategy for crutches used to operate paraplegic exoskeletons. With Hyundai Medical Exoskeleton (H-MEX) and its controller crutch, we conducted an experiment performing a series of movements with 30 subjects followed by post-interviews. With regard to previous design of crutches, significant design issues such as operational logic and button layout were identified. We suggest HMI strategies to improve the crutch in four specific directions: simple operation, comfortable shape and arrangement, clear information feedback, and enhanced convenience. A new design has been proposed by applying the HMI strategy and will help patients more effectively by reducing burden and fatigue when using crutch.